Microplastics extraction from wastewater treatment plants: Two-step digestion pre-treatment and application. (15th February 2023) - Zhang, Ziqi; Liu, Wenzong; Gao, Qun; Huang, Fang; Kang, Yuanyuan; Pan, Yusheng; Luo, Gaoyang; Zhou, Xu; Fan, Lu; Wang, Aijie; Gao, Shu-Hong
Highlights: The two-step digestion pre-treatment was developed and optimised to efficiently extract MPs. The identification of aged nonbiodegradable MPs was not affected after digestion. MLSS and MLVSS interfere most with MPs extraction. WWTPs in Shenzhen had higher concentrations of MPs. Rayon, polyester and PP were the most frequently detected MPs in the effluent. Abstract: As the gathering place of urban wastewater, wastewater treatment plants (WWTPs) are indispensable for removing microplastics (MPs), one of the emerging contaminants of great concern, from cities into the natural environment. A reliable and efficient extraction method for MPs, especially in organic-rich matrices, such as sludge samples, is the basis for studying MPs contamination, while it is still lacking. The digestion process, which requires further optimisation, is the most important step during extraction. In this study, we developed and optimised a two-step digestion process to extract MPs and proposed a recommended dosage of digestion reagents based on the mixed liquid volatile suspended solids (MLVSS) level of the sample. Successive addition of 30% H2 O2  + 1 M HNO3 (v: v  = 1:1, T  = 60 °C, t  = 5 h  + 5 h) could efficiently extract MPs from sludge samples (over 90%), and the recommended dosage of digestion reagent was 100 ml 30% H2 O2 +100 ml 1 M HNO3 with the sample MLVSS lower than approximately 0.43 g. This new method was also applied to examine the characteristics of MPs in two typical WWTPs (anaerobic-anoxic-oxic and biofilter processes) in Shenzhen. The concentrations of MPs in the influent, effluent and dewatered sludge were approximately 114.00 n/L, 6.00 n/L, and 126.00 n/g (dry weight) in WWTP A, whereas 404.00 n/L, 22.00 n/L, and 204.00 n/g (dry weight) in WWTP B, respectively. Rayon and polyester were the dominant polymers in both the WWTPs. Fibers accounted for the largest proportion of the influent and effluent. Sizes between 0.20–0.50 mm were most detected. This study provides a new and efficient reference method to extract MPs from WWTPs samples, especially sludge sample, with less MPs loss and more beneficial to subsequent identification. Graphical abstract: Image, graphical abstract